Diurnal and light-regulated expression of AtSTP1 in guard cells of Arabidopsis - Stadler, Ruth; Büttner, Michael (Plant physiology, 2003)
Guard cell chloroplasts are unable to perform significant photosynthetic CO2 fixation via Rubisco. Therefore, guard cells depend on carbon supply from adjacent cells even during the light period. Due to their reversible turgor changes, this import cannot be mediated by plasmodesmata. Nevertheless, guard cells of several plants were shown to use extracellular sugars or to accumulate sucrose as an osmoticum that drives water influx to increase stomatal aperture. This paper describes the first localization of a guard cell-specific Arabidopsis sugar transporter involved in carbon acquisition of these symplastically isolated cells. Expression of the AtSTP1 H+-monosacharide symporter gene in guard cells was demonstrated by in situ hybridization and by immunolocalization with an AtSTP1-specific antiserum. Additional RNase protection analyses revealed a strong increase of AtSTP1 expression in the dark and a transient, diurnally regulated increase during the photoperiod around midday. This transient increase in AtSTP1 expression correlates in time with the described guard cell-specific accumulation of sucrose. Our data suggest a function of AtSTP1 in monosaccharide import into guard cells during the night and a possible role in osmoregulation during the day.